2016
DOI: 10.3168/jds.2015-10395
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fractionated colostrum replacer and vitamins A, D, and E on haptoglobin and clinical health in neonatal Holstein calves challenged with Mycobacterium avium ssp. paratuberculosis

Abstract: Thirty Holstein calves were obtained from 2 dairy farms in central Iowa at birth and randomly assigned to 1 of 6 treatment groups: (1) colostrum deprived (CD), no vitamins; (2) colostrum replacer (CR), no vitamins; (3) CR, vitamin A; (4) CR, vitamin D3; (5) CR, vitamin E; and (6) CR, vitamins A, D3, E, with 5 calves per treatment in a 14-d study. Calves were fed pasteurized whole milk (CD) or fractionated colostrum replacer (CR) at birth (d 0) and injected with vitamins according to treatment group. From d 1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 28 publications
3
13
3
Order By: Relevance
“…This finding was more evident in CD calves compared to CR calves and relates to increased likelihood of clinical scours and depression. We previously noted that CD calves had greater occurrence of these clinical signs [16], conforming to the paradigm for dysbiosis [46]. This correlates with the higher burden of Campylobacter observed for CD calves.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…This finding was more evident in CD calves compared to CR calves and relates to increased likelihood of clinical scours and depression. We previously noted that CD calves had greater occurrence of these clinical signs [16], conforming to the paradigm for dysbiosis [46]. This correlates with the higher burden of Campylobacter observed for CD calves.…”
Section: Discussionsupporting
confidence: 59%
“…This is an interesting observation as we were expecting that vitamins would improve tissue integrity thereby helping to thwart pathogen invasion. Calves in the present study had more than adequate serum levels of retinol, 25-(OH)-D 3 , and α-tocopherol by day 14, averaging 255 ng/mL, 97 ng/mL, and 2800 µg/mL, respectively [16], suggesting that deficiency of vitamin E was not the causative factor for this trend. Although vitamin E plays significant roles as an anti-oxidant and an immunomodulatory agent [40,41], a comprehensive study of dairy cows in the Netherlands found that feeding 3000 IU/day of vitamin E combined with high plasma levels of vitamin E at dry-off led to an increased incidence of mastitis [42].…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…A central APR-upregulated hepatic protein, haptoglobin, has strong antioxidant activity (Quaye, 2008) and plays a role in suppressing inflammation (Huntoon et al, 2008;Krueger et al, 2016;Wang et al, 2001). Carotenoids have been found to influence hepatic proteins (Ben-Dor et al, 2005;Zhang et al, 1992) that are upregulated during the APR (Hart, 1988).…”
Section: Introductionmentioning
confidence: 99%